Development of the method of non-destructive analysis of heavy metals in the raw material that contains carbohydrates - Mayboroda, Elena; Mazur, Larisa (My University, 2016)
The effect of specific carbohydrates (matrices) on the results of analysis of microelement in the feedstock has been investigated. Some samples of carbohydrates (mono-, di- and polysaccharides), containing various amounts of salts Cd, Zn, Pb and Hg, have been studied.
Keywords: carbohydrates; metal identification; визначення металів; вуглеводи; кафедра харчової хімії